The Implementation of Game-Based Learning to Enhance Students’ Speaking Skills in Indonesian EFL Classrooms: English - Iwan Dudy Gunawan (JOEY: Journal of English Ibrahimy, 2025)
This study examined the application of non-digital Game-Based Learning (GBL) to improve speaking skills in an Indonesian EFL vocational classroom. The study utilized three interactive games—role play cards, board game speaking, and picture description—to provide an enjoyable and accessible alternative to conventional instruction, thereby enhancing students' oral communication skills. It employed a Classroom Action Research (CAR) framework across three cycles with 26 tenth-grade students. Data were gathered through speaking performance assessments, classroom observations, and student surveys. The results demonstrated continuous improvement in five speaking components: fluency, vocabulary, grammar, pronunciation, and confidence. The most significant gains were noted in vocabulary and confidence, indicating that frequent engagement in communicative, low-anxiety activities promoted student involvement and risk-taking. Observational data corroborated this trend, revealing heightened participation and interaction as students became more accustomed to the game formats. Furthermore, students' feedback reflected favorable attitudes toward GBL, highlighting its role in increasing the enjoyment and motivation of speaking practice. These findings indicated that non-digital game-based learning was a practical and pragmatic approach for enhancing speaking skills, particularly in resource-constrained educational settings. The study advocated for the integration of GBL into English as a Foreign Language (EFL) speaking instruction to enhance student engagement, communication, and confidence, and suggested further research into combining digital and traditional games for broader pedagogical impact.